Regional and socioeconomic distribution of household food availability in Brazil, in 2008-2009 - Levy, Renata Bertazzi; Claro, Rafael Moreira; Mondini, Lenise; Sichieri, Rosely; Monteiro, Carlos Augusto (Revista de Saúde Pública, 2012)
OBJECTIVE: To describe the regional and socioeconomic distribution of household food availability in Brazil. METHODS: Data from the 2008-2009 Household Budget Survey on food and beverage acquisition for household consumption, conducted by the Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistics), were analyzed. The amounts of foods, recorded during seven consecutive days in the 55,970 sample households, were converted into calories and nutrients. Food quality indicators were constructed and analyzed according to the regional and socioeconomic strata of the Brazilian population. RESULTS: The amount of energy from protein was adequate in all regional and socioeconomic strata. On the other hand, an excess of free sugars and fats was observed in all regions of the country, especially in the Southern and Southeastern regions. The proportion of saturated fats was high in urban areas and consistent with the greater contribution of animal-derived products. Limited availability of fruits and vegetables was found in all regions. An increase in the fat content and reduction in carbohydrate content of the diet were observed with the increase in income. CONCLUSIONS: The negative characteristics of the Brazilian diet observed at the end of the first decade of the 21st century indicate the need to prioritize public policies for the promotion of healthy eating.